2016
DOI: 10.1080/10903127.2016.1247200
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Prehospital Misinterpretations of ST Elevation Myocardial Infarction

Abstract: To determine the causes of software misinterpretation of ST elevation myocardial infarction (STEMI) compared to clinically identified STEMI to identify opportunities to improve prehospital STEMI identification. Methods: We compared ECGs acquired from July through June 2012 using the LIFEPAK 15 on adult patients transported by the Los Angeles Fire Department. Cases included patients ≥18 years who received a prehospital ECG. Software interpretation of the ECG (STEMI or not) was compared with data in the regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…Of note, acute coronary angiography is often included in the evaluation of patients with takotsubo cardiomyopathy because of elevated cardiac biomarkers and its STEMI-like ECG appearance [26,27]. Besides ECG artifacts, perimyocarditis and ERS were the most common causes of false-positive software interpretations of STEMI in a prehospital study with >40.000 patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, acute coronary angiography is often included in the evaluation of patients with takotsubo cardiomyopathy because of elevated cardiac biomarkers and its STEMI-like ECG appearance [26,27]. Besides ECG artifacts, perimyocarditis and ERS were the most common causes of false-positive software interpretations of STEMI in a prehospital study with >40.000 patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that a cardiologist or medical doctor overview and confirmation improves diagnostic accuracy [ 21 ], while treatment delays are not increased [ 22 ]. In particular, ECG artefacts will then be avoided [ 23 ]. Our observation of an improved sensitivity to diagnose acute MI through the combination of automated ECG interpretation and expert consultation is in agreement with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…While the various agencies in our EMS system use different brands of cardiac monitors for acquiring 12-lead ECGs, there is significant heterogeneity in the test characteristics of computerized STEMI diagnosis between brands 1721. Transmission of the ECG was at the discretion of the treating paramedic.…”
Section: Limitationsmentioning
confidence: 99%